Factors Affecting the Preparation of Government Financial Statements: Application of Government Accounting Standards, Utilization of Information Technology, and Internal Control System (Literature Review of State Financial Management) - Cris Kuntadi; Cipto Juwanto; Muhammad Irvan Zakaria (Dinasti Publisher, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and penomena of relationships or influences between variables. This article aims to review the factors affecting the preparation of government financial statements, namely: the application of government accounting standards, the use of information technology and internal control systems, a literature study of State Financial Management. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this literature review article are: 1) The application of Government Accounting Standards affects the Preparation of Government Financial Statements, 2) The use of Information Technology affects the Preparation of Government Financial Statements, 3) The Internal Control System affects the Preparation of Government Financial Statements.